The Role and Importance of Social Studies in The Education of Gifted Students - Çal, Ülkü Tuğçe; Demirkaya, Hilmi (Journal of History Culture and Art Research, 2020)
The purpose of this research is to disclose the opinions of teachers who work in BILSEM about the importance and position of social studies education in gifted students’ instruction. In this study phenomenology design from qualitative research methods is used. In the determination of the study’s participants criterion sampling was grounded on. The research’s participants consist of 19 teachers from varied branches who work in the subsidiary of Antalya Provincial Directorate of National Education, BILSEM. The research’s data are gathered through semi-structured interviews and obtained data are analyzed with the thematic analysis technique. The opinions of the participant teachers about this research were analysed under various categories. In the research it was revealed that participating teachers think about social studies’ place in society as an adaptation to social life, creating citizenship awareness, cultural values, teaching history and geography, and developing communication skills. They see the position of social studies in the instruction of gifted and talented students as creating citizenship awareness, socializing and developing verbal intelligence, improving skills of leadership and creativity and being an explorer-questioner, redounding and developing multiple perspectives. It was found that participating teachers evaluated the social studies’ necessity in gifted student’s instruction with regard to developing their interests and abilities, socializing and developing verbal intelligence, adaptation to social life, contribution to the learning of social science disciplines and developing high level cognitive qualities.